A three-phase dual-input matrix converter for grid integration of two AC type energy resources - Liu, Xiong (2013)
This paper proposes a novel dual-input matrix converter (DIMC) to integrate two three-phase ac type energy resources to a power grid. The proposed matrix converter is developed based on the traditional indirect matrix converter under reverse power flow operation mode, but with its six-switch voltage source converter replaced by a nine-switch configuration. With the additional three switches, the proposed DIMC can provide six input terminals, which make it possible to integrate two independent ac sources into a single grid-tied power electronics interface. The proposed converter has input-to-output voltage boost capability since power flows from the converter's voltage source side to its current source side. Commanded currents can be extracted from the two input sources to the grid. The proposed control and modulation schemes guarantee sinusoidal input and output waveforms as well as unity input power factors. The simulation and experimental results using a laboratory prototype are provided to validate the effectiveness of the proposed control and modulation schemes for the proposed converter.